Standardizing CRISPR-Cas13 knockdown technique to investigate the role of cdh2 gene in pituitary development through growth hormone expression and transcription factors - Ventura Fernandes, Bianca Helena; Junqueira, Mara S.; MacRae, Calum; Silveira de Carvalho, Luciani R. (Frontiers in Endocrinology, 2024)
Introduction: Congenital hypopituitarism (CH) is characterized by the deficiency of pituitary hormones. Among CH patients, 85% lack a molecular diagnosis. Whole Exome Sequencing (WES) identified a homozygous variant (c.865G>A, p.Val289Ile) in the CDH2 gene, responsible for N-Cadherin production, crucial for cell-cell adhesion. Predicted to be likely pathogenic, the variant was found in a patient deficient in GH, TSH, ACTH, and LH/FSH. Its impact on cell adhesion was confirmed in L1 fibroblast cell lines. Objective: Create a cdh2 knockdown in zebrafish for investigating its role in pituitary development through growth hormone and transcription factors expression. Methods: Utilized pET28B-RfxCas13d-His plasmid for Cas13 mRNA production via in vitro transcription, guiding Cas13 to cdh2 with three RNAs. Injected the complex into single-cell embryos for analysis up to 96 hpf. Assessed gene expression of cdh2, prop1, pit1, and gh1 using RT-qPCR. Evaluated cdh2 protein expression through the western blot technique. Results: Knockdown animals displayed developmental delay. The cdh2 expression decreased by 75% within 24 hours, rebounded by 48 hours, and reached wild-type levels by 96 hpf. gh1 expression decreased at 48h but increased by 96 hpf, aligning with WT. No significant differences in prop1 and pit1 expression were observed. Conclusion: Our findings underscore cdh2's role in pituitary development and hormonal regulation, offering insights for developmental biology research.